Peran Elit Lokal dalarn Reintegrasi Gerakan Aceh Merdeka (GAM) Pasca MoU Helsinki - M. Hamdan Basyar (Pusat Penelitian Politik, 2008)
Reintegration is not an easy task There are economics politics social and psychological problems from ex combatants when they have to reintegrate with its societies Due to the complexities of reintegration problems it needs comprehensive continued and synergy cooperation among them From field research there are some conditions that need to be addressed in order to create a good reintegration program Firsth it needs to create conditions that could build integrative behaviour from some groups towards implementation of Helsinki MoU Secondly it needs to build democracy infrastructure at local level as instrument of transfunction conflict Thirdly it needs central government consistency towards integration implementation with economic basis through some programs that could transform conflict from armed conflict into political struggle Fourthly it needs to strengthen the infrastructure ofreintegration implementer institution and also to prepare transfer ofresponsibilities from central to local government Fifthly all of stakeholders in Aceh need to be endorsed to actively participate in the reintegration program in order to create a permanent conflict resolution Sixthly the reintegration program need to be built continously not only limited to compensation find In this sense the program do not act as charity but as for strengthening the economic of ex combatants and other conflict vitims The program was hoped to overcome poverty and can be implemented continously Therefore it would need an independent controller institution in order to have an appropriate reintegration program.